Preparation of nitrogen-doped carbon quantum dots and its application as a fluorescent probe for Cr(vi) ion detection. (20th March 2019) - Luo, Xiaomin; Bai, Pengxia; Wang, Xuechuan; Zhao, Guohui; Feng, Jianyan; Ren, Huijun
Abstract : A facile synthetic method was used to prepare N-CQDs via the hydrothermal treatment of gelatin. Abstract : A facile synthetic method was used to prepare N-CQDs via the hydrothermal treatment of gelatin. The obtained N-CQDs were characterized by FTIR spectroscopy, XPS, TEM and UV-vis spectrometry; the results showed that the N-CQDs have been successfully prepared. Importantly, we designed a "turn off" fluorescent probe for the detection of Cr(vi ) ions; the results indicated that when the concentration of N-CQDs was 10 μg mL −1, the pH was 9 and the reaction time was 20 min at room temperature, the fluorescence quenching degree of N-CQDs was relatively large. The results indicated that N-CQDs showed a wide linear range from 0 to 60 μmol L −1, with a low limit of detection of 348.18 μmol L −1 . Furthermore, this method and the diphenylcarbazide method were respectively used to detect Cr(vi ) ions in leather and the results were compared, which were satisfactory. It can be seen that this method was simple, low cost and had a higher sensitivity and better selectivity.